Theoretical-political trends of social assistants on Facebook - Morsch, Caroline; Maria Baptista Lewgoy, Alzira (Argumentum, 2021)
The article presents the theoretical-political trends of social assistants in publications and comments on the Facebook pages of the Federal Council for Social Service and Libertarian Social Service from 2016 to 2018. It is a qualitative, quantitative, and documentary research, whose results indicate the continuity of the Marxist perspective and the emergence of pragmatic, neoconservative and functionalist-systemic perspective, which eclectically converge against Marxism and the Ethical-Political Project, under liberal ideopolitical unity.